2015
DOI: 10.3758/s13421-015-0581-8
|View full text |Cite
|
Sign up to set email alerts
|

Relational integrativity of prime-target pairs moderates congruity effects in evaluative priming

Abstract: In evaluative priming, positive or negative primes facilitate reactions to targets that share the same valence. While this effect is commonly explained as reflecting invariant structures in semantic long-term memory or in the sensorimotor system, the present research highlights the role of integrativity in evaluative priming. Integrativity refers to the ease of integrating two concepts into a new meaningful compound representation. In extended material tests using paired comparisons from two pools of positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 51 publications
2
8
1
Order By: Relevance
“…As the pronunciation task is a relatively pure index of semantic activation (Balota and Lorch 1986), these findings suggested that the affective meaning may be parasitic on the semantic meaning. The nonsignificant affective priming effect in the low associative strength condition was consistent with the findings of Ihmels et al (2016). They found that the processing facilitation of prime-congruent targets could only appear when the prime and target words could be integrated into a meaningful concept.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…As the pronunciation task is a relatively pure index of semantic activation (Balota and Lorch 1986), these findings suggested that the affective meaning may be parasitic on the semantic meaning. The nonsignificant affective priming effect in the low associative strength condition was consistent with the findings of Ihmels et al (2016). They found that the processing facilitation of prime-congruent targets could only appear when the prime and target words could be integrated into a meaningful concept.…”
Section: Discussionsupporting
confidence: 91%
“…In Experiment 1, the absence of the affective priming effect in the ‘low associative strength’ condition may be due to the reduced activation of the corresponding semantic representations. However, the absence of the affective priming effect in the ‘low associative strength’ condition in Experiment 1 seemed to be inconsistent with the results of Ihmels et al (2016); they found a significant affective priming effect in a LDT task when the prime and target word pairs were associatively unrelated but not when they are related (Experiment 3). The inconsistency may be due to the methodological difference.…”
Section: Discussioncontrasting
confidence: 69%
See 3 more Smart Citations